Experimental and Theoretical Studies on the Creep Behavior of Bayer Red Mud - Baoyun Zhao; Wei Huang; Zhile Shu; Mengmeng Han; Yanbo Feng (Advances in Civil Engineering)
Long-term stability and safety of the Bayer red mud (BRM) disposal field is very important for the local residents’ life, which necessitates the knowledge of its creep behavior. In order to investigate the creep behavior of BRM, a series of triaxial drained creep tests were conducted by using an improved triaxial creep apparatus. The results indicate that the creep behavior of BRM is significant with confining and deviatoric stresses being critical factors. The creep strain is in a nonlinear relationship with stress and time, and a larger deviator stress will lead to a larger creep strain. The main failure mechanism of BRM is plastic shear, accompanied by a significant compression and ductile dilatancy. Based on the test results, two well-established creep models, the Burgers creep model and Singh–Mitchell creep model, were used to comparatively analyze the creep behavior of the Bayer red mud under a certain stress level. Then, an improved Burgers creep damage constitutive model with the addition of a damage variable was proposed, whose parameters were also analyzed in detail. The comparison of the calculated values of the creep model and the experimental values shows that the proposed creep damage model can better describe the instant elastic deformation, attenuation creep, steady-state creep, and accelerated creep stages of the Bayer red mud.